When Are You Going to Marry? Intention to Marry through the Lens of Theory of Planned Behavior and Self-Regulatory Focus - Koçak, A.; Mouratidis, A. (Turkish Psychological Counseling and Guidance Journal, 2024)
What makes people to take important decisions in their lives, such as marriage? To answer this question, we relied on theory of planned behavior to examine the degree to which peoples' attitudes, subjective-norms, and behavioral control perceptions predict their intentions to marry. Furthermore, we used self-regulatory focus theory to examine whether such attitudes, norms, and perceptions could be partly explained by peoples' focus on pursuing-gains versus securing non-losses. We conducted a cross-sectional, web-based survey with a sample of 699 Turkish young adults (70.7% females; Mage =24.89 years, SD = 4.31). The results of the structural equation modeling showed that promotion-focus positively and prevention-focus negatively related to perceived behavioral control, which in turn negatively related to intentions to marry. Intentions also related positively to attitudes but not to subjective-norms, which however related positively to promotion-focus and negatively to prevention-focus. Gender and age differences were also found. The results are discussed in light of the two theories. © 2024 The Authors. Turkish Journal of Counseling Psychology and Guidance is published by Turkish Psychological Counselling and Guidance Association.
Keywords: Marriage intention; prevention-focus; promotion-focus; self-regulatory focus theory; theory of planned behavior